Characterization of the complete mitochondrial genome of Oryzaephilus surinamensis Linne (Insecta: Coleoptera: Silvanidae) from Xichuan - Liang, Sheng (Mitochondrial DNA B Resour, 2019)
The saw-toothed grain beetle, Oryzaephilus surinamensis Linné, is a well-known stored-product insect. Beetles were obtained from Xichuan County and the mitochondrial genome was characterized (GenBank accession number MN535903). The mitogenome consists of a circular DNA molecule of 15,941 bp, with only 27.36% GC content. It comprises 13 protein-coding, 22 tRNA, and 2 rDNA genes. The protein-coding genes have typical ATN (Met) initiation codons and are terminated by typical TAN stop codons.